SELF EFFICACY SEBAGAI PREDIKTOR SCHOOL WELL-BEING SISWA SMP ISLAM DI KOTA BEKASI - Dwi Reza Syahril; Yulia Fitriani (CV. ADIBA ASIHA AMIRA, 2025)
Students require a good school well-being to enhance their comfort, happiness, and reduce fear in the school environment. Therefore, students must possess high self- efficacy to manage their emotions, impulses, and behaviors. This study aims to analyze the impact of self-efficacy on students' school well-being. The research method used is a quantitative approach with cluster sampling technique, involving 127 respondents. The data analysis results show a significant correlation between self-efficacy and school well-being, ranging from 0.328 to 0.648 for self-efficacy and 0.328 to 0.605 for school well-being, which exceeds the significance threshold of 0.3. The correlation coefficient of 0.805 identifies a very strong relationship between self-efficacy and school well-being. This indicates that self-efficacy plays a role as one of the predictors of school well-being in students. Therefore, it is hoped that the development of self-efficacy aspects in students can be carried out in various ways. With increased self-efficacy, students are expected to demonstrate confidence and self-assurance while in the school environment